Bi- and tetraflavonoids from Aristolochia ridicula - Carneiro, FJC; Boralle, N.; Silva, DHS; Lopes, LMX (Elsevier B.V., 2000)
From stems of Aristolochia ridicula, two biflavones, four unusual chalcone-flavone dimers and one tetraflavonoid were isolated. The structures of the seven compounds were elucidated by spectroscopic methods. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: Aristolochia ridicula; Aristolochiaceae; flavonoids; biflavonoid; tetraflavonoid